Homologous and heterologous antigenic matched vaccines containing different H5 hemagglutinins provide variable protection of chickens from the 2014 U.S. H5N8 and H5N2 clade 2.3.4.4 highly pathogenic avian influenza viruses. Issue 46 (1st November 2017) - Kapczynski, Darrell R.; Pantin-Jackwood, Mary J.; Spackman, Erica; Chrzastek, Klaudia; Suarez, David L.; Swayne, David E.
Highlights: Vaccine protection was best demonstrated by inactivated vaccines with close HA similarity. Recombinant vaccines protected a majority of birds after lethal challenge. Viral shedding from vaccinated birds was generally lower in groups receiving inactivated vaccines. These studies provide support for the use of vaccines with close match to the clade 2.3.4.4 HA. Abstract: From December 2014 to June 2015, a novel H5 Eurasian A/goose/Guangdong (Gs/GD) lineage clade 2.3.4.4 high pathogenicity avian influenza (HPAI) virus caused the largest animal health emergency in US history resulting in mortality or culling of greater than 48 million poultry. The outbreak renewed interest in developing intervention strategies, including vaccines, for these newly emergent HPAI viruses. In these studies, several existing H5 vaccines or vaccine seed strains with varying genetic relatedness (85–100%) to the 2.3.4.4 HPAI viruses were evaluated for protection in poultry. Chickens received a single dose of either an inactivated whole H5 AI vaccine, or a recombinant fowl poxvirus or turkey herpesvirus-vectored vaccines with H5 AI hemagglutinin gene inserts followed by challenge with either a U.S. wild bird H5N8 (A/gyrfalcon/Washington/40188-6/2014) or H5N2 (A/northern pintail/Washington/40964/2014) clade 2.3.4.4 isolate. Results indicate that most inactivated H5 vaccines provided 100% protection from lethal effects of H5N8 or H5N2 challenge. In contrast, the recombinant live vectored vaccines only provided partial protection which ranged from 40 to 70%. Inactivated vaccine groups, in general, had lower number of birds shedding virus and at lower virus titers then the recombinant vaccine groups. Interestingly, prechallenge antibody titers using the HPAI challenge viruses as antigen in heterologous vaccine groups were typically low (≤2 log2 ), yet the majority of these birds survived challenge. Taken together, these studies suggest that existing vaccines when used in a single immunization strategy may not provide adequate protection in poultry against the 2.3.4.4 HPAI viruses. Updating the H5 hemagglutinin to be genetically closer to the outbreak virus and/or using a prime-boost strategy may be necessary for optimal protection.